Preoperative Gargling with Magnesium Sulphate versus Lignocaine on Postoperative Sore Throat in Patients Undergoing Surgery under General Anaesthesia: A Randomised Clinical Study - Jatin Patel; Yashvi Samir Patwa; Pooja Shah; Rajsi Shah; Sara Mary Thomas (Journal of Clinical and Diagnostic Research)
Introduction: Patients frequently experience throat pain after undergoing surgical procedures that require tracheal tube insertion, leading to patient discomfort. Various methods are employed to prevent Postoperative Sore Throat (POST), including preoperative gargling with Magnesium Sulphate and Lignocaine. These agents act through different mechanisms, with potential implications for intraoperative haemodynamic stability. Aim: To compare the effectiveness of preoperative gargling with Magnesium Sulphate (20 mg/kg) versus Lignocaine (4 mg/kg of 2%) in reducing POST and to assess the influence of these agents on intraoperative haemodynamic parameters. Materials and Methods: In this randomised, double-blinded prospective clinical study at tertiary care centre Dhiraj Hospital, Department of Anaesthesiology, Smt. Bhikhiben Kanjibhai Shah Medical Institute and Research Centre, Sumandeep Vidyapeeth Deemed to be University, Gujarat, India, from October 2022 to November 2023, 70 adult patients {ages 18-65 years, American Society of Anaesthesiologists (ASA) I and II} undergoing surgery under general anaesthesia with endotracheal intubation were enrolled. They were randomly assigned to two groups of 35 each: Group M (Magnesium Sulphate, 20 mg/kg in 20 mL of 5% dextrose solution) and Group L (Lignocaine, 4 mg/kg of 2% Lignocaine in 20 mL sterile water). Both groups gargled for 30 seconds, 15 minutes prior to induction. Demographic data, haemodynamic parameters, and POST scores were compared across different time points intraoperatively (5, 15, 30, 45, 60, 90, 120 minutes) and postoperatively (0, 1, 2, 4, 6, 8, 12, and 24 hours). Statistical analysis was performed using an unpaired Student’s t-test for numerical data and a Chi-square test for categorical data. Paired t-tests were used for comparisons within groups. Results: Both Magnesium Sulphate and Lignocaine significantly reduced the incidence of POST (p-value <0.05). However, Magnesium Sulphate was found to be more effective than Lignocaine in preventing POST (p-value <0.05). Additionally, Magnesium Sulphate was associated with better haemodynamic stability, as assessed by intraoperative blood pressure and heart rate measurements. No significant differences in adverse events were noted between the groups. Conclusion: Preoperative gargling with Magnesium Sulphate was more effective than Lignocaine in reducing POST and contributed to better haemodynamic stability during surgery. These findings suggest that Magnesium Sulphate may be a superior option for reducing postoperative discomfort and improving patient outcomes in surgeries requiring general anaesthesia with tracheal intubation.